The certainty on how schema influences students’ writing in gathering ideas: Reconstructing schema theory - SuryaSatyawati; Nasmilah; MokogintaKarmila (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
Learning other cultures requires someone to understand attributes of cultural understanding, including concepts of religion, values and beliefs, and customs or traditions. In fact, not everyone is familiar with the other culture, even their own culture. Sometimes, they use their schema or background knowledge when they are involved in discussing it. This research intends to find whether Piaget’s theory of Schema is still relevant to the conditions and situations because of the advanced technology. A change in students’ habits might cause a difference in their learning. This research aims to ascertain how schema influences students’ writing process, including the gathering and managing of ideas and information. There were 24 students from the English Literature Department and 33 from the English Department of Mulawarman University participating in the research. Quantitative data was obtained to determine whether the students did assimilation and/or accommodation. The data were gained by using questionnaires with 2 points Likert-Scale. Meanwhile, the analysis of whether schema influenced students’ writing process was calculated using a percentage, and the results were shown using diagrams. The results show that accommodation has more influence or impact than assimilation. This indicates that students nowadays change schemas to fit the new information.